MANAJEMEN ASRAMA SEBAGAI MEDIA PENDIDIKAN KARAKTER BAGI SISWA KELAS BOARDING DI MTS NEGERI 2 KARANGANYAR - Kurniawan, Adi; Suyatman, Suyatman (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
This study aims to describe dormitory management as a medium for character education for boarding-class students at MTs Negeri 2 Karanganyar, focusing on three main aspects: planning, implementation, and evaluation of dormitory development programs. This research employs a descriptive qualitative approach, with the research subjects consisting of the dormitory head, supervising teachers, and dormitory students. Data were collected through interviews, observations, and documentation, while data analysis used the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that dormitory management planning is carried out through the formulation of the vision, mission, and activity programs that emphasize the development of religious, disciplined, independent, and cooperative character. The implementation of these programs is reflected in various daily activities, such as congregational prayers, Quran recitation, cleanliness routines, structured study schedules, as well as communal work and other collaborative activities. Furthermore, the evaluation of dormitory management is conducted regularly through supervisors’ meetings and observation of student behavior, focusing on changes in attitude and improvements in students’ daily discipline. Through well-planned and continuous dormitory management, the boarding environment at MTs Negeri 2 Karanganyar has proven to be an effective medium for instilling Islamic character values and shaping students to become religious, disciplined, independent, and cooperative individuals. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan manajemen asrama sebagai media pendidikan karakter bagi siswa kelas boarding di MTs Negeri 2 Karanganyar, dengan fokus pada tiga aspek utama, yaitu perencanaan, implementasi, dan evaluasi program pembinaan asrama. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan subjek penelitian terdiri atas kepala asrama, guru pembina, dan siswa penghuni asrama. Teknik pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi, sedangkan analisis data menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa perencanaan manajemen asrama dilakukan melalui penyusunan visi, misi, dan program kegiatan yang fokus pada pembentukan karakter religius, disiplin, mandiri, dan kerja sama. Implementasi program tersebut diwujudkan dalam berbagai kegiatan harian, seperti shalat berjamaah, tadarus, kegiatan kebersihan, jadwal belajar terarah, serta kerja bakti dan aktivitas kebersamaan lainnya. Selanjutnya, evaluasi manajemen asrama dilaksanakan secara berkala melalui rapat pembina dan observasi perilaku siswa, dengan penekanan pada perubahan sikap serta peningkatan kedisiplinan siswa dalam kehidupan sehari-hari.Melalui pengelolaan asrama yang terencana dan berkesinambungan, lingkungan boarding di MTs Negeri 2 Karanganyar terbukti menjadi wadah efektif dalam menanamkan nilai-nilai karakter Islami dan membentuk kepribadian siswa yang religius, disiplin, mandiri, serta mampu bekerja sama dengan baik.